2008
DOI: 10.1002/app.27366
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of novel polyurethanes based on N1,N4‐bis[(4‐hydroxyphenyl)methylene]succinohydrazide hard segment

Abstract: Objective The protective effect of HLA–DRB1 alleles on the development of rheumatoid arthritis (RA) is poorly understood. The aim of this study was to perform a meta‐analysis of 4 European populations to investigate which HLA–DRB1 alleles are associated with protection in anti–citrullinated protein antibody (ACPA)–positive RA and ACPA‐negative RA. Methods Data for >2,800 patients and >3,000 control subjects for whom information on HLA–DRB1 typing and ACPA status was available were collected from 4 European cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 37 publications
4
30
0
Order By: Relevance
“…Overall, in the current study, DSC data are in good agreement with our earlier reports [21,22,29,30].…”
Section: Thermal Propertiessupporting
confidence: 95%
See 2 more Smart Citations
“…Overall, in the current study, DSC data are in good agreement with our earlier reports [21,22,29,30].…”
Section: Thermal Propertiessupporting
confidence: 95%
“…The emission spectra from these diols and PUs have appeared around 364-375 nm and 462-485 nm, respectively [29]. From the absorption and emission spectra, it can be concluded that there is no significant difference in ODBNMD and hard-segmented PUs and that the observed absorption and emission spectral data are in close agreement with the previous reports [29,30].…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Absorption peaks observed around 265 nm are attributed to the p-p* transition of the localized benzenoid ring. 43,44 From the absorption spectra, it is concluded that there is no significant difference in the three PUs of this study. The absorption peak of BDO-extended PU (265 nm) exhibited a slight red shift in wavelength compared with that of Dow BPU (263 nm), while the absorption peak of silk-inspired PU (266 nm) exhibited a farther slight red shift in wavelength compared with that of BDO-extended PU (265 nm).…”
Section: Uv-vis Absorption Spectramentioning
confidence: 86%
“…Previous articles from our laboratories [1][2][3][4][5] -bis[(4-hydroxyphenyl)methylene]-succinohydrazide as hard segments. As a continuation of those studies, we present here the preparation schemes and characterization of eight novel types of PUs, based on similar, previously developed diols, 1,2 that were produced through changes in the position of the hydroxyl groups and the use of different aliphatic dialdehydes instead of diamine units as hard segments of the PUs.…”
Section: Introductionmentioning
confidence: 99%